PENGARUH TITIK AKUPUNKTUR ST 18, GB 21, CV 17 TERHADAP PENINGKATAN VOLUME ASI IBU MENYUSUI DI BPS E MALANG - Leny Candra Kurniawan (Jurnal Kesehatan Hesti Wira Sakti, 2019)
Abstract Breast milk is the best food for a baby the early life, this is not only breast milk has many contains of the nutrients for the baby needs but it also contains immunologic substances that protect the baby from infection. The Indonesian Government has launched The Exclusive Breastfeeding Movement for 0-6 months infants who given breast milk only without other foods and drinks. Exclusive breastfeeding can reduce the number of infant mortality in Indonesia. Various efforts are made to increase the breast milk volume by taking drugs and herbs / traditional herbs. However, it causes some side effects. Another traditional way that is relatively safe is acupuncture therapy, which jabs acupuncture needles at some point to get the benefit for the body. This research is to determine the acupuncture points ST18, GB21, CV17 effects to increase the breastmilk volume in breastfeeding mothers. This research was conducted at “E” Midwife Private Practice in Malang. The research design used pre-experimental design with pretest-posttest design. The population of this research are all breastfeeding mothers who visited at “E” BPS in June 2016 are 35 people and samples taken as many as 15 people. The sampling technique using purposive sampling technique. From the research results has known the effect of acupuncture at point ST 18, GB 21, and CV 17 to increase the breast milk of breastfeeding mothers at E Midwife Private Practice in Malang. The calculation using SPSS statistic 21 with paired sample t test obtained result of significant value (0.00)